Dark Energy as a Key Player in the Evolution of Cosmic Objects - Harutyunian, H. A.
Researchers have been searching for the speed at which the universe’s expansion is slowing for decades. The dominant cosmological model predicted the inevitable process of braking. The discovery of the opposite process should have alerted researchers. However, the basic cosmological model has not changed at all. Although it is estimated that approximately 70 percent of all existing mass energy is dark energy, its role is not fully understood. In this paper, we show that the evolution of cosmic objects and their systems at all hierarchical levels occurs due to the interaction of ordinary matter with dark energy. Moreover, the interaction also increases the mass of ordinary matter. The mass increase occurs due to the conversion of some part of the dark energy into mass. Namely, it happens both due to a decrease in the mass defect of atomic nuclei and because of the fission of the same nuclei. It is noted that the role of dark energy should be studied much deeper than is currently being done, considering the known laws of physics.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture